2014
DOI: 10.1016/j.biocel.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning causes an increase in glucose transporter-4 levels in mononuclear cells in sled dogs

Abstract: This study was designed to investigate the effects of physical conditioning on the expression of the insulin sensitive glucose transporter 4 protein (GLUT4) on mononuclear cells and HOMA-IR levels in dogs and compared to results reported in human skeletal muscle and the skeletal muscle of rodent models. Blood was sampled from conditioned dogs (n=8) and sedentary dogs (n=8). The conditioned dogs were exercised four months prior the experiment and were following a uniform training protocol, whereas the sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 36 publications
(39 reference statements)
1
26
1
Order By: Relevance
“…It still remains unclear whether exercise and muscle contraction, which stimulates GLUT4 translocation locally, would also have an effect on the expression or translocation of GLUT4 in circulating mononuclear. In a previous study we have shown that four months of long term conditioning significantly increased GLUT4 content in mononuclear cells of sled dogs [25] . The present study was undertaken to address the question of whether the observed increase in skeletal muscle GLUT4 protein after one acute bout of exercise, measured by highly invasive biopsies, can also be measured in peripheral mononuclear cells, assessed via minimally-invasive blood sampling, to further examine the potential use of this technique as reliable and feasible technique in a clinical setting.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…It still remains unclear whether exercise and muscle contraction, which stimulates GLUT4 translocation locally, would also have an effect on the expression or translocation of GLUT4 in circulating mononuclear. In a previous study we have shown that four months of long term conditioning significantly increased GLUT4 content in mononuclear cells of sled dogs [25] . The present study was undertaken to address the question of whether the observed increase in skeletal muscle GLUT4 protein after one acute bout of exercise, measured by highly invasive biopsies, can also be measured in peripheral mononuclear cells, assessed via minimally-invasive blood sampling, to further examine the potential use of this technique as reliable and feasible technique in a clinical setting.…”
Section: Introductionmentioning
confidence: 84%
“…The protocol for the assessment of GLUT4 protein concentrations translocated to the surface of mononuclear cells has been described elsewhere [25] . We controlled for the measurement of GLUT4 translocated to the cell membrane, and not total GLUT4, in comparing sonicated to unsonicated samples.…”
Section: Methodsmentioning
confidence: 99%
“…Because GHbA1c is associated with long-term elevated glucose levels and since these dogs were not at risk for diabetes, we evaluated TNF in the next part of the study and investigated the effect of weight gain. Our previous finding that conditioning increased the insulin sensitive glucose transporter, GLUT4, in mononuclear cells of sled dogs prompted our initial inquiry on the effects of exercise on other biomarkers associated with insulin resistance (Schnurr et al, 2014;. TNF and adiponectin were measured in the sedentary sled dogs after weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Sled dogs are at low risk for developing T2D; their increased energy expenditure when compared to other elite athletes, make them an ideal model for studying the effects of exercise and metabolism (Hinchcliff et al, 2000). Recent work in our lab has shown that both acute and chronic exercise increases GLUT4, the insulinsensitive glucose transporter, in mononuclear cells of sled dogs (Schnurr et al, 2014;. Therefore, the aim of this present study was to investigate the effects of exercise or weight gain separately on biomarkers associated with insulin resistance in sled dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The quanti cation of GLUT4 expression on the surface of peripheral blood lymphocytes might be a potentially useful method for the early detection of individuals at a high risk of diabetes (35,36). GLUT4 levels in peripheral blood mononuclear cells have been investigated using indirect immuno uorescence in sled dogs (37), and in ammatory monocyte populations in humans (38)(39)(40), which could be used as a method to estimate the in uence of insulin on GLUT protein translocation and the dynamics of glucose uptake. GLUT4 was also detected in granulocytes and could be used to assess the immune response in diabetes (41) or the response of the plasma membrane to insulin during infection (33,42).…”
Section: Discussionmentioning
confidence: 99%